Factors Influencing Student Decisions: A Study on Price, Location, and Promotion at Pangeran Antasari Educational Foundation - Mexenro Gerael Hutagaol; Farah Jihan Nabila; Hendry, Hendry; Nasib, Nasib (International Journal of Economics, Business and Innovation Research, 2025)
This study seeks to ascertain the influence of price, location, and promotional elements on student decision-making. The study's demographic and sample comprised students from the Pangeran Antasari Foundation, totaling 100 respondents. The sample method employed was non-probability sampling utilizing a purposive approach. This study employs a quantitative methodology characterized by a descriptive and verification approach, utilizing multiple linear regression analysis for data analysis. Hypothesis testing concurrently use the F-test and partially utilizes the t-test. The findings of this study demonstrate that the promotion, price, and location variables collectively exert a positive and significant influence on purchasing decisions. Additionally, each variable promotion, price, and location individually has a positive and significant impact on purchasing decisions.